Applying sport management practices to the SME business context: The perspectives of leadership and employee engagement - Tulonen, Veeti (My University, 2024)
The factors essential to this thesis include the continuous globalization across all business sectors and the pioneering status of the sport industry has embarked upon in terms of internationalizing operations. Moreover, the practices of leadership and employee engagement have yet been rather insufficiently addressed within the context of small and medium-sized enterprises (SMEs). The innovative approaches observed in the sport context appear to have partial applicability to SME organizations. This thesis examines the roles and duties of SME managers and sport organization managers, focusing on their leadership and employee engagement practices within both the SME and sport industry contexts. It also discovers what kind of challenges a context to another practice transfer might face. Existing literature indicates that SME managers and sport managers differ in their job duties, skill sets and roles. Although leadership is a well-researched concept in business studies, there is a lack of consensus on its definition the scholars. Employee engagement, typically defined as an employee’s emotional commitment to the organization and its goals, is a well-established term. However, current research does not combine sport and SME context and see what kind of a potential there might be in sport context for SME management. Therefore, the research question of this thesis asks how the SME business managers can benefit from managerial practices in leadership and employee engagement used by managers in sport industry. Additionally, the sub-questions focus on defining the SME manager and sport manager, examining their differences and similarities, and exploring the concepts of leadership and employee engagement and also the practical perspective to those in SME and sport organizations. Moreover, implementation challenges are examined. Empirical part of this study discovers the same topics through expert interviews and thematic analysis. The findings clearly indicate that several managerial practices from sport industry could be effectively applied to SME organizations. It is suggested that collective and servant leadership, highlighted organizational culture, developed rewarding systems and arranging off-time activities to employees could make SME organizations more effective in leadership and employee engagement. Implementation challenges are solved by concentrating on interfaces, making sure that everyone knows their own role, and other’s role, in implementation process and committing everyone to the change. This research offers contribution to theory and practical suggestions to managers.
Keywords: SME management, Sport management, Leadership, Employee engagement, challenges of implementation, practice transfer